KETEGARAN TOKOH MELIA DALAM NOVEL DI SINI CINTA PERTAMA KALI BERSEMI KARYA MIRA W. DALAM DUNIA PENDIDIKAN - Ikha Listyarini (Universitas PGRI Semarang, 2014)
Popular culture (popular culture) is the culture created by ordinary people with simple and intended for commercial purposes, so it can be enjoyed by the whole society. Popular culture (popular culture) is one part of the realm of cultural studies (cultural studies) because popular culture is also part of a culture that enrich the culture of any society. In the span of a long history, created a popular culture that has produced popular literature which has a high magnetic power to the audience of literary or lovers who simply looking for entertainment. Conditions that hit many aspects of life, not least in the literature. Originally came from the birth of popular art, which later developed into popular fiction stories circulating lately. In popular literature stories told not to show an intense problem, because if so, the popular literature will be heavy and can turn into serious literature.Novel Love it Here First Bersemi reached a circulation of 10,000 and suffered five reprints. After the success of his novel, Wim Umboh working on this novel into a film of the same title and was also sold in the market in the '80s with a cast-famous actor. This is one sign that the novel is a work of popular literature, which is reproduced through a variety of media. In this way, it is hoped this story can be enjoyed by the wider community, not just lovers of literature community.Kink is inside of Melia can be applied in education. Actualization of the value in the formation of character through education requires careful planning and mature so that the process and the results are as expected. Planting process in the formation of character values ?óÔé¼ÔÇ??óÔé¼ÔÇ?through education must be packaged well and that can be implemented through a structured learning, extracurricular activities, and the activities of governance (management). Given the character education is part and an integral part of the development of national character, the role of education is vital and has a major responsibility for generating human resources Indonesian character that can conduct a civilized nation of Indonesia.